ANALIS EMPIRIS PELAYANAN PUBLIK DI KABUPATEN BUOL PROVINSI SULAWESI TENGAH - Paerah, Andi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The issue in this study is related to the tendency of public service quality in Indonesia that are decreasing recently. This case triggers Employee ASN to continue to increase the performance for the sake of getting back the citizen’s belief in term of public services. The purpose of this study is to test empirically how far the effect of spiritual leadership, organizational support and emotional Intelligence on employee performance with mediation job satisfaction and organizational citizenship behavior. This study used quantitative method and the data analysis method used Structural Equation Models (SEM) technique with Analysis of Moment Structure (AMOS) 21 version, which had 223 employee samples. The result of this study shows ASN performance is influenced by emotional intelligence, organizational support, leadership and employee behaviour, while job satisfaction has no significant effect on employee performance. The result of importance this study reference to make or consideration in decision making for OPD leaders related to ASN performance